Properties of health wine from fuit pulp of Balayong (Cassia Fistula Linn.). - Voloso, Ailyn Pomasin (2003.)
The fruit pulp of "balayong", Cassia fistula L. is a non-toxic raw material for wine making. Cytotoxicity test using Brine Shrimp Assay showed that the crude ethanolic extract has a LC50 higher than 1000 ug/mL., In the fermentation process, the first seven days was the peak of yeast activity as indicated by a significant change in the specific gravity, pH, and total acidity of the must. Bioactivity studies on "balayong" wines and crude ethanolic extract showed that it has a notable anti-inflammatory as well as antispasmodic activity. Using the Carragenan-Induced edema Method, the 30% sugar added must and crude ethanolic extract has the highest percentage inhibition of 57.45 and 63.50%, respectively. The wines wth 20% and no sugar added usts also caused 51.06 and 36.17% inhibition, respectively. Using the Cahrcoal Tracing Assay, the wine with 30% sugar added must has the highest antispasmodic activity of 30.1% traveled by charcoal. The crude ethanolic extract and the wines with 20% and no sugar added must also exhibited 50.0, and 58.7% traveled, respectively. Chemical analysis on "balayong" fruit pulp and wines showed that it contained a notable amount of Vitamin C. Using the Iodometric method, the fruit pulp contained 931.84 ppm Vitamin C and the wines contained 158.83, 148.99 ppm and 82.93 ppm Vitamin C for 0, 20, and 30 % sugar added musts, respectively. Qualitative analysis of sugar showed that the fruit pulp of "balayong" contained sucrose.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Balayong -- Fruit Pulp; Cassia Fistula Linn